Advancing the study of political cleavages through experimentation: Revisiting regionalism and redistributive preferences in Canada. Issue 2 (15th March 2017) - Davidson, Adrienne; Lesch, Matthew; Héroux-Legault, Maxime; Whyte, Tanya; Asaf, Zain; Czuba, Karol; Porisky, Alesha
ABSTRACT: The maintenance of welfare state policies requires citizen support for the provision of a social safety net through taxation and redistribution. Research has shown that a diverse political polity presents a risk to the welfare state; however, Canada bucks the trend and does not see citizen support for economic redistribution decline in response to immigration-based population diversity. Using Canada as our case, we argue that scholars of welfare state politics and redistribution should turn their attention to other sources of population heterogeneity in an effort to better understand how different political cleavages affect citizens' redistributive preferences. We use an online experimental survey to manipulate the in-group identity of 500 Canadians. The survey enables respondents to identify with other in-group identities along regional, linguistic, income-group, and urban/rural characteristics. Our results find that while Canadians do have a strong baseline preference for redistributive behaviour, regional and linguistic cleavages moderate this outcome.